A Study on the Vegetation and Carbon Stocks of the Special Purpose Forest (KHDTK) of Senaru Village, Northern Lombok - Muhamad Husni Idris; Sitti Latifah; Irwan Mahakam Lesmono Aji; Endah Wahyuningsih; Indriyatno Indriyatno; Rima Vera Ningsih (Jurnal Ilmu Kehutanan)
Study was conducted in Forest for Special Purpose (Education Forest) ±225.7 ha in Senaru Village, North Lombok. The study was aimed to determine the potential of vegetation and carbon stocks. Land cover of study area was changed due to the timber management in 1993, planting mahogany and sengon in 1996, planting Aquilaria spin 1998-2001, and currently the implementation of agroforestry. Population for this study was the area of education forest intensively utilized by farmer (±120 ha). Sampling was determined by means of random with the intensity of 1% and distributed into 30 plots of 20x20m. Data analysis included analysis of vegetation, above ground carbon and soil carbon stock. The result shows that 32 species were found. There were 10, 8, 17 and 20 species of vegetation for seedlings, saplings, poles and trees, respectively. The first two highest Important Value Index (IVI) for seedling and saplings were Coffea sp and Theobroma sp, where the IVI for seedling was 120.3 and 34.2, while for saplings were 146.1 and 92.5. Erytrhina sp and Pharaseriantes sp were the two highest IVI for poles and trees, where the IVI for poles was 77.9 and 48.7, while for trees was 87.1 and 79.9, respectively. Carbon stock of study area was 126.41 ton C/ha, which was differentiated into carbon stock for saplings (3.36 ton C/ha), pole (9.32 ton C/ha), trees (70.61 ton C/ha), understory (0.13 ton C/ha), litter (0.29 ton C/ha) and soil (42.7 ton C/ha). The results of this study could be an input in develoving a model of Senaru educational forest as wells as future evaluation. Besides, it could enrich the existing information about forest resources.